Navigating access to safe water by rural households in sub-Saharan Africa: Insights from north-western Ghana - Issah Baddianaah; Alfred Dongzagla; Sakibu Nakyeenaa Salifu (Sustainable Environment)
Households’ access to safe drinking water remains a forlorn hope in sub-Saharan Africa because of the continuous deterioration in water quality and quantity. The impacts on livelihoods are particularly dire for rural households who are at high risk of collecting unsafe and insufficent water. In our quest to provide safely managed water services for all by 2030 as envisioned by SDG target 6.1, knowledge of rural households’ water collection experiences and challenges are essential for policy decisions on rural water supply. Yet, few studies have explored how rural households navigate access to safe drinking water. Our study draws on a descriptive survey design, involving face-to-face semi-structured interviews and observation to gain insight on how rural households in the Siriyiri community of Ghana access drinking water. Critical water access challenges unpacked in the study were long distances to water sources, high water collection time, high cost of buying water and head portage of water amidst concerns about the water being contaminated. Inadequate access to safe drinking water in rural communities, and the Siriyiri community in particular, is exacerbated by dysfunctional hand pump boreholes, the main source of water supply. Households cope with water insecurity through water storage, collection of water from privately-owned sources, building of water infrastructure (self-supply), re-use of wastewater, dependence on multiple water sources and travelling to distant locations to collect water. Based on the findings, the Community Water and Sanitation Agency, and District Assemblies should provide network water systems that are accessible on premises or via standpost in all water-stressed rural communities.